2009
DOI: 10.1080/02786820902718078
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Biodiesel-Diesel and Ethanol-Diesel on the Particulate Emissions of a Direct Injection Diesel Engine

Abstract: Experiments were conducted on a 4-cylinder direct-injection diesel engine using ultralow sulfur diesel blended with biodiesel or ethanol to investigate the particulate emissions of the engine under five engine loads at the maximum torque engine speed of 1800 rpm. Four biodiesel blended fuels and four ethanol blended fuels with oxygen concentrations of 2%, 4%, 6%, and 8% were used. With the increase of oxygen content in the blended fuels, the brake specific fuel consumption becomes higher and the brake thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 32 publications
2
25
1
Order By: Relevance
“…While for each engine speed, regardless of the mode of fueling the engine, the fraction of both nano-particles and ultrafine particles decreases with increase in engine load, indicating that the particles tend to be larger in size with increasing engine load. Similar results can also be found in Di et al (2009) for blended fuels. Probably, with an increase of engine load, the increase of particle concentration enhances particle collision and agglomerations, resulting in the formation of larger particles and a reduction in the fraction of nano-particles and fraction of ultrafine particles.…”
Section: Particle Number Concentrationsupporting
confidence: 77%
See 1 more Smart Citation
“…While for each engine speed, regardless of the mode of fueling the engine, the fraction of both nano-particles and ultrafine particles decreases with increase in engine load, indicating that the particles tend to be larger in size with increasing engine load. Similar results can also be found in Di et al (2009) for blended fuels. Probably, with an increase of engine load, the increase of particle concentration enhances particle collision and agglomerations, resulting in the formation of larger particles and a reduction in the fraction of nano-particles and fraction of ultrafine particles.…”
Section: Particle Number Concentrationsupporting
confidence: 77%
“…At each engine speed, there is an increase in PM mass concentration with engine load. At the engine speed of 1920 rev/min, for different level of fumigation methanol, the PM mass concentration varies from 8.7 to 11.8 mg/m 3 for the engine load of 0. also be found in Ning et al (2004), Cheng et al (2008), and Di et al (2009). Also, for the same engine load, the PM mass concentration in general increases with increase in engine speed.…”
Section: Smoke Opacity and Particulate Mass Concentrationsmentioning
confidence: 53%
“…NO x are a regulated emission in the vehicles because they contribute to photochemical smog, acid rain and ground level ozone. Many authors have indicated that the usage of biodiesel decreases the emissions of HC, CO and PM and the improvements are mainly due to the higher oxygen content of the fuels compared to diesel fuel (Gordon et al, 2014;Di et al, 2009;Karavalakis et al, 2009;Lapuerta et al, 2008;Mayer et al, 2005). A reduction in the organic aerosol emissions was also observed with 10% biodiesel blend and with 30% biodiesel blend as reduced by 22% and 21% than Diesel (Chirico et al, 2014).…”
Section: Introductionmentioning
confidence: 52%
“…(43) Although 1-dodecanol (47)(48)(49)(50) and n-butanol (51) are adopted in the ethanol-diesel blend as emulsifier in many studies on the performance and emissions of diesel engine fuelled with ethanol-diesel blends, the discussion for these works will be excluded in this review because spray characteristics of e-diesel was not included in these studies. It is usually blended with conventional diesel denoted as DEXX that XX will be ethanol percentage in volume of ethanol in diesel.…”
Section: Spray Characteristics Of Ethanol Blended Fuelsmentioning
confidence: 99%